Education for the 21st century and the new demands of modern capital: reflections from the perspective of Zygmunt Bauman (Práxis Educativa, 2025)
This study aims to analyze the influence of the Delors Report (1999) on the concept of education envisioned for the 21st century, seeking to understand how its ideas have impacted contemporary education in light of the demands of modern capital, and to generate reflections from the perspective of Zygmunt Bauman. The discourse analysis, grounded in Bauman’s critical sociology and that of other authors, is expected to reveal how the Delors Report is tied to the concept of modernity in this century and its implications for education and the current world of work. Based on bibliographic research and theoretical foundations drawn from the works of Bauman (1998, 1999a, 1999b, 2000, 2021a, 2021b), this study seeks to foster self-awareness, understanding, and individual responsibility in order to promote autonomy and freedom – ultimately aiming to critically examine the terms and goals set for 21st-century education and the new globalized capitalist market, enabling a deeper understanding of how the world works in order to act within it.Keywords: Education. Zygmunt Bauman. Delors Report.